1976
DOI: 10.1128/aac.10.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Quantitation of Experimental Surgical-Wound Infections Used to Evaluate Topical Antibacterial Agents

Abstract: Reproducible experimental surgical-wound infections in mice for use in the evaluation of topical antibacterial agents are described. The experimental wound was created on the backs of mice by means of a midline incision and was infected by means of cotton sutures monocontaminated with Staphylococcus aureus or Pseudomonas aeruginosa. The course of these wound infections was followed by quantitation of surface bacteria through use of a surface rinse technique. Surface wound counts of the infecting organisms thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
45
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 18 publications
(13 reference statements)
1
45
0
Order By: Relevance
“…The murine model of skin wound infection is established by implanting contaminated sutures (29) and represents the secondary skin infections that may occur following damage by accidental trauma, surgery, and burns or as a result of superinfection of an underlying skin disease. Such foreign-body infections are a stringent test of the efficacy of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The murine model of skin wound infection is established by implanting contaminated sutures (29) and represents the secondary skin infections that may occur following damage by accidental trauma, surgery, and burns or as a result of superinfection of an underlying skin disease. Such foreign-body infections are a stringent test of the efficacy of antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…The discriminative models utilized in the studies reported here have been used previously for evaluating systemic and topical antimicrobial agents (5,6,14,29), and the data have been shown to correlate well with efficacy in humans. The results reported here show that the new cream formulation of mupirocin was as effective as the established ointment preparation and, in two of eight trials, it was more efficacious for treating staphylococcal and streptococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…The technique used for production of the wound was similar to that described by McRipley and Whitney (15). A length of suture was run under the skin on the back of each mouse under anesthesia, so that a 1-cm length of suture lay between the skin layers and the panniculus carnosus.…”
Section: Micementioning
confidence: 99%
“…In the preceding paper experimental surgical-wound infections in mice were described and characterized (6). In addition, a rapid method for quantitating bacteria in the wound infections was presented.…”
mentioning
confidence: 99%
“…Details of the experimental Staphylococcus aureus and Pseudomonas aeruginosa surgical-wound infections were presented in the preceding paper (6). aliquots of wound washings and bacterial inocula containing 50 to 300 viable organisms were placed on brain heart infusion agar plates and spread over the surface of the agar.…”
mentioning
confidence: 99%